Pregabalin vs. gabapentin in the treatment of neuropathic pain: a comprehensive systematic review and meta-analysis of effectiveness and safety - Víctor Mayoral; Rafael Galvez; Marta Ferrándiz; Xoán Miguéns Vázquez; Carlos Cordero-García; Antonio Alcántara Montero; Concepción Pérez; María Pérez-Páramo (Frontiers in Pain Research)
IntroductionNeuropathic pain is a prevalent and burdensome condition, and both pregabalin and gabapentin are widely used for its treatment. However, there is a lack of clarity regarding their comparative efficacy and safety. This meta-analysis aims to evaluate and compare the effectiveness and safety of pregabalin vs. gabapentin in managing neuropathic pain.MethodsThis study followed PRISMA guidelines and employed the PICOS search strategy. Comparative studies (clinical trials and cohort studies) were included, with patients with neuropathic pain treated either with pregabalin or gabapentin. Primary outcomes assessed were efficacy and safety. Data were extracted from PubMed, Embase, Scopus, and the Cochrane Collaboration Library databases. The risk of bias was evaluated using the Cochrane Review Manager tool. Statistical analysis was performed using Review Manager 5.4.1 software, calculating effect sizes and conducting sensitivity analysis based on medication dosage.ResultsA total of 14 studies with 3,346 patients were analyzed. Pregabalin showed superior results compared to gabapentin in the Visual Analog Scale (VAS) at various time intervals up to 12–14 weeks (SMD −0.47, 95% CI −0.74 to −0.19). The pregabalin group also had significant improvements in SF-12/SF-36/EQ-5D scores (SMD 0.39, 95% CI 0.11–0.68) and experienced more days with no/mild pain (MD 9.00, 95% CI 8.93–9.07) and fewer days with severe pain (MD −3.00, 95% CI −4.96 to −1.04). Pregabalin resulted in lower opioid consumption (OR 0.50, 95% CI 0.33–0.76). Gabapentin had a higher incidence of nausea and vomiting. Sensitivity analysis supported the efficacy of pregabalin.ConclusionIn conclusion, pregabalin demonstrated superior and faster efficacy in alleviating neuropathic pain than gabapentin did. Additionally, it improved patient-reported outcomes, resulted in lower opioid consumption, and led to fewer adverse events.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=565208, PROSPERO (CRD42024565208).